Phylogenetic Analysis and Fungicide Baseline Sensitivities of Monilia mumecola in China - L. F. Yin (2019)
Monilia mumecola is one of the causal agents of peach brown rot in China. In this study, M. mumecola isolates from different locations and hosts were used to analyze the genetic diversity and to assay the sensitivity to four generally used fungicides: carbendazim, tebuconazole, azoxystrobin, and boscalid. Results showed that isolates from different locations tended to be separated. Interestingly, isolates from different hosts (e.g., peach and apricot) at the same locations generally clustered together, indicating that the M. mumecola isolates may infect different hosts in the same areas. The fungicide sensitivity assay of 93 M. mumecola isolates showed that the average effective concentration for 50% mycelial growth inhibition values for carbendazim, tebuconazole, azoxystrobin, and boscalid were 0.103, 0.034, 0.325, and 0.419 µg/ml, respectively. The sensitivity distributions of the tested isolates to the four fungicides showed continuous unimodal curves, indicating no qualitative shift of resistance. No significant difference of sensitivity to tested fungicides was observed among isolates from either different locations or different hosts.